SPLIT NASIONALISME GENERASI MUDA PAPUA DI KOTA JAYAPURA : PERSPEKTIF TEORI IDENTITAS - Sabara, Sabara (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2018)
This article explores the issue of split nationalism among Papuan young generation. This research was conducted to prove the pre-assumption that young generation of Papua are holding double nationalism. This research raises two main questions. First, how the Papuan and Indonesian identities are constructed among the Papuan young generation? Second, how is the modelling of Indonesian nationalism among the Papuan young generation? The issue of Papuan identity is always observed vis-à-vis Indonesian identity among Papuan young generation, which creates paradoxical manners and split identity leading to liminal identity of being both Indonesian and Papuan. Identifying Papuans as having Christian Melanesia roots against Indonesians’ Muslim Malays in one hand, and Papuans’ traumatic historical experiences of being discriminated and unequally treated on the other hand, have defined these two identities in paradox. This research shows that among some Papuan origins, possessing double nationalism of being Indonesian and Papuan at the same time is still apparent. Some other informants, however, have shown their awareness that Papuan identity should be fully integrated and merged into one positive and constructed Indonesian nationalism.